2014
DOI: 10.3109/21691401.2014.897631
|View full text |Cite
|
Sign up to set email alerts
|

Heparin removal from human plasma using molecular imprinted cryogels

Abstract: In this study, heparin-imprinted poly(hydroxyethyl methacrylate-N-[(3-dimethylamino)-propyl] methacrylamide) cryogel column (HpMIP) was synthesized for removal of Hp from human plasma using molecular imprinting technique. Hp removal studies were performed from both aqueous solution and human plasma. Selectivity studies were performed using fast protein liquid chromatography (FPLC) system. The obtained results showed that the HpMIP column can remove Hp from both aqueous solutions and human plasma samples select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 43 publications
(41 reference statements)
1
14
0
Order By: Relevance
“…The precomplex amount designates the amount of molecular cavities in the MIPs directly; because the protein C specific nanocavities were obtained after the removal of the protein C from the synthesized pcMIPs. If the precomplex amount is high, then the cavities come together and the combined cavities not allowed the optimum adsorption due to the lack of 3‐D recognition . Moreover, the synthesized pcMIPs were not stable in higher amounts of the precomplex in the polymer receipt.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The precomplex amount designates the amount of molecular cavities in the MIPs directly; because the protein C specific nanocavities were obtained after the removal of the protein C from the synthesized pcMIPs. If the precomplex amount is high, then the cavities come together and the combined cavities not allowed the optimum adsorption due to the lack of 3‐D recognition . Moreover, the synthesized pcMIPs were not stable in higher amounts of the precomplex in the polymer receipt.…”
Section: Methodsmentioning
confidence: 99%
“…The swelling tests were performed to characterize the water uptake behavior of the cryogels . The swelling ratios were detected by placing dried cryogel samples in 50 mL of water.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Baydemir et al have synthesized heparin (Hp) molecular imprinted cryogels, in which N ‐[3‐dimethylamino)‐propyl] methacrylamide was the cationic functional monomer and heparin was the template. The results of selectivity studies showed that HpMIP column could successfully 90% of Hp from 28 U mL −1 of human plasma samples …”
Section: Biological Molecular Imprinting With Different Scalementioning
confidence: 99%
“…The results of selectivity studies showed that HpMIP column could successfully 90% of Hp from 28 U mL −1 of human plasma samples. [168] "Epitope" Imprinting: Epitope imprinting are introduced in detail in the abovementioned protein imprinting. [169,170] Owing to amphiphilic and high molecular weight of poly saccharides, it is difficult to prepare MIPs by using the entire poly saccharides as a template.…”
Section: Polysaccharides Imprintingmentioning
confidence: 99%
“…Molecular imprinting (MI) method encompass design and synthesis of novel materials which are capable of recognizing proteins and other biological assemblies, such as whole cells and viruses and have potential fundamental and practical applications [10][11][12][13]. Specific applications of such materials include down-stream bioprocess for the purification of biopharmaceuticals, drug delivery, diagnostics, sensors, etc.…”
Section: Introductionmentioning
confidence: 99%